Congenital Nail Disorders among Children with Suspected Ectodermal Dysplasias - Maier-Wohlfart, Sigrun; Aicher, Carmen; Willershausen, Ines; Peschel, Nicolai; Meißner, Udo; Gölz, Lina; Schneider, Holm (Genes, 2022)
We report on a cohort of 204 children referred between January 2017 and January 2022 to the German Center for Ectodermal Dysplasias, Erlangen. The most frequent reasons for referral were tooth malformations and lack of multiple teeth leading to the suspicion of an ectodermal dysplasia. Many patients also suffered from being unable to perspire. Nail abnormalities, in contrast, represented a much rarer finding, albeit the impact on some individuals was large. As ectodermal dysplasias are congenital genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands, we analyzed congenital nail disorders detected in these patients. Dystrophic or otherwise abnormal nails were evident in 17 of 18 subjects with pathogenic WNT10A or GJB6 variants but in none of 161 children with EDA variants underlying X-linked hypohidrotic ectodermal dysplasia. However, 2 of 17 children who carry mutations in EDAR or EDARADD, two other genes involved in the ectodysplasin A signaling pathway, showed nail abnormalities, such as brittle or hypoplastic nails. TP63 variants were regularly associated with nail disorders. In one girl, anonychia congenita caused by a compound heterozygous variant of the R-spondin-4 gene (RSPO4) was diagnosed. Thus, nail dysplasia is rarer among patients with ectodermal dysplasia than commonly thought.
CRIS-Team Scopus Importer:2022-12-09
Keywords: anonychia/hyponychia congenita; congenital nail disorders; ectodermal dysplasia; R-spondin 4 (RSPO4)

Exhausted Lag-3+ CD4+ T cells are increased in pediatric Inflammatory Bowel Disease. - Schnell, Alexander; Aicher, Carmen; Schnegelsberg, Philipp; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Rueckel, Aline; Regensburger, Adrian; Wölfle, Joachim; Hörning, André (Clinical and Experimental Immunology, 2025)
T cells are one of the main drivers of inflammatory bowel diseases (IBD). Infliximab (IFX) is used in the treatment of IBD as an anti-inflammatory drug to induce remission by neutralizing TNFα. We determined the individual chemokine/homing receptor and cytokine profile in pediatric IBD patients before and during IFX therapy to identify predictive biomarkers for therapy success. Peripheral blood CD4+ cells from pediatric patients with IBD were immunomagnetically isolated and either directly analyzed by FACS for cell distribution and chemokine/homing receptor expression or evaluated for cytokine production after in-vitro-stimulation. Twenty-one responders (RS) and 21 non-responders (NRS) were recruited. Before IFX therapy, flow cytometry revealed decreased percentages of naïve conventional T cells in pediatric IBD patients. The proportions of CD62-L+ T cells were decreased in both CD and UC therapy responders. The cytokine profile of T cells was highly altered in IBD patients compared to healthy controls (HC). During IFX therapy, the frequencies of conventional memory and regulatory memory T cells expanded in both cohorts. IFX response was marked by a decrease of α4β7+ and IFNγ+ memory T cells in both CD and UC. In contrast, frequencies of Lag-3+ T cells proved to be significantly increased in NRS. These observations were irrespective of the underlying disease. T cells of pediatric IBD patients display an activated and rather Th1/Th17-shifted phenotype. The increased expression of the checkpoint molecule Lag-3 on T cells of NRS resembles a more exhausted phenotype than in RS and HC which appeared to be a relevant predictive marker for therapy failure.
EVALuna2:582625